2012
DOI: 10.1111/j.1365-2567.2012.03625.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular determinants of CD8 co‐receptor function

Abstract: Summary CD8+ T cells respond to signals mediated through a specific interaction between the T-cell receptor (TCR) and a composite antigen in the form of an epitopic peptide bound between the polymorphic a1 and a2 helices of an MHC class I (MHCI) molecule. The CD8 glycoprotein 'co-receives' antigen by binding to an invariant region of the MHCI molecule and can enhance ligand recognition by up to 1 million-fold. In recent years, a number of structural and biophysical investigations have shed light on the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 79 publications
0
59
0
Order By: Relevance
“…Moreover, we have observed previously that CD8αβ strengthens pMHC monomer binding on cloned CTL to various degrees, depending on the TCR (19). Collectively these findings suggest that the contribution of CD8 to pMHC binding depends on the TCR sequence, i.e., on different TCR-pMHC docking modes, allowing different degrees of CD8 coengagement (23,26,27,45). Although in our system all CD8 + T cells expressed the P14 TCRβ chain, previous structural studies indicated that pMHC footprints on TCR can vary considerably, depending on the TRAV and CDR3α sequences (24,45,46,47).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, we have observed previously that CD8αβ strengthens pMHC monomer binding on cloned CTL to various degrees, depending on the TCR (19). Collectively these findings suggest that the contribution of CD8 to pMHC binding depends on the TCR sequence, i.e., on different TCR-pMHC docking modes, allowing different degrees of CD8 coengagement (23,26,27,45). Although in our system all CD8 + T cells expressed the P14 TCRβ chain, previous structural studies indicated that pMHC footprints on TCR can vary considerably, depending on the TRAV and CDR3α sequences (24,45,46,47).…”
Section: Discussionmentioning
confidence: 60%
“…5 A and B). In canonical "diagonal" docking of TCR to pMHC, the CDR1α and CDR2α loops are poised to interact with the MHC α2 helix (23)(24)(25)(26)(27)45). This canonical docking mode is imposed by the coreceptor CD8αβ, which, by coengaging TCRassociated pMHC, elicits CD3 phosphorylation by CD8-associated lck and thereby promotes thymic selection of CD8 + T cells (1,6,45,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), as anticipated by previous tetramer dissociation assays (22,30). Interestingly, the CD8 stabilization factor was independent of the TCR-pMHC affinity, in contrast with the CD8 dependence for T-cell activation, which can be directly linked to the affinity (3,20,22), and allows tuning the sensitivity and specificity of T-cell responses (34).…”
Section: Discussionmentioning
confidence: 71%
“…The TCR/CD3 complex usually operates in concert with a co-receptor, which is CD8 for MHCI-restricted TCRs and which is thought to assist in the weak-type interactions 10 , via several modes of action, such as enhancement of TCR/pMHCI stability 11,12 and delivery of Lck to TCR/CD3 13 . These effects tend to (i) prolong the average duration of a TCR/pMHCI contact and (ii) reduce the time required for the ITAMs to become phosphorylated and trigger intracellular signalling, both of which can enhance efficacy of weak ligands but which may equally well reduce that of strong ligands 14 .…”
Section: Introductionmentioning
confidence: 99%